GRB10 rs1800504 Polymorphism Is Associated With the Risk of Coronary Heart Disease in Patients With Type 2 Diabetes Mellitus - Yang, Yang; Qiu, Wentao; Meng, Qian; Liu, Mouze; Lin, Weijie; Yang, Haikui; Wang, Ruiqi; Dong, Jiamei; Yuan, Ningning; Zhou, Zhiling; He, Fazhong (Frontiers in Cardiovascular Medicine, 2021)
Diabetic vascular complications are one of the main causes of death and disability. Previous studies have reported that genetic variation is associated with diabetic vascular complications. In this study, we aimed to investigate the association between GRB10 polymorphisms and susceptibility to type 2 diabetes mellitus (T2DM) vascular complications. Eight single nucleotide polymorphisms (SNPs) in the GRB10 gene were genotyped by MassARRAY system and 934 patients with type 2 diabetes mellitus (T2DM) were included for investigation. We found that GRB10 rs1800504 CC+CT genotypes were significantly associated with increased risk of coronary heart disease (CHD) compared with TT genotype (OR=2.24; 95%CI: 1.36-3.70, p=0.002). Consistently, levels of cholesterol (CHOL) (CC+CT vs TT, 4.44±1.25 vs 4.10±1.00mmol/L; p=0.009) and low density lipoprotein cholesterin (LDL-CH) (CC+CT vs TT, 2.81±1.07 vs 2.53±0.82mmol/L; p=0.01) in T2DM patients with TT genotype were significant lower than those of CC+CT genotypes. We further validated in MIHA cell that the total cholesterol (TC) level in GRB10-Mut was significantly reduced compared with GRB10-WT; p=0.0005. Likewise, the reversed palmitic acid (PA) induced lipid droplet formation in GRB10-Mut was more effective than in GRB10-WT. These results suggest that rs1800504 of GRB10 variant may be associated with the blood lipids and then may also related to the risk of CHD in patients with T2DM.